У меня в груди Анюта: Рассказы и повесть / А. Д. Дорофеев - Дорофеев Александр Дмитриевич (Внеклассное чтение, 2008)
7-9кл Экземпляры: аб. ДБ (2008) / Инвентарный номер: 55324 / Цена: / Авт.знак: Д 69 / ББК: 84(2Рос)